Analisis Logam Berat Dalam Daun Sirsak dan Daun Beluntas - Sabaniah Indjar Gama (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2017)
The Research about heavy metal that is contained in Medicine herbs has been. The soursop leaves and beluntas leaves has been analyzed metal content by atomic absorption spectrophotometer. The Results show that the concentration of Pb is 0392 ppm in soursop leaves and 0,026 ppm in beluntas leaves. The concentrations of Cd metal is 0,0263 in soursop leaves and 0.0523 ppm in beluntas leaves. it can be concluded that heavy metals Pb and Cd in some medicin herbs do not exceed the maximum limit of the Pb <10 ppm Cd <0.30 ppm.